The Access to and Use of ICT in Learning English: A Case of University Students - Adeliani, Cici; Harahap, Alamsyah; Sofyan, Dedi; Kurniawan, Ildi; Lubis, Azhar Aziz (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
This research aimed to find out the studentsÃ¢â‚¬â„¢ access to ICT application and how far ICT application helps students in mastering English language skills faced by English students of English Education Study Program at the University of Bengkulu in the 2020/2021 academic year. This research was an explanatory sequential mixed methods design. The population of this research was English students of English Education Study Program at the University of Bengkulu. The sample of this research was selected by using purposive sampling technique, totaling 80 students for questionnaire and 24 students for interview. The data were collected by using questionnaire and interview. The instruments were consisted of 15 items adapted from Dang Hoang Tri and Nhung Hong Thi Nguyen (2014). This research used Microsoft Excel to analyze the data.Ã‚Â The result of this study showed that students access 15 ICT applications in English learning. Also, researcher found that the majority of students have positive perception towards ICT application can help students in mastering English language skills.